Cross section of the 96Zr(α,n)99Mo reaction induced by α-particles beams on natZr targets; Applied Radiation and Isotopes; Vol. 166 - Villa Pineda N. E. Nelson Enrrique; Skuridin V. S. Viktor Sergeyevich; Golovkov V. M. Vladimir Mikhailovich; Garapatski A. A. Alexander Alexandrovich (2020, 2020)
Title screen